::OMPARATIVE STUDIES ON THE CANNING PROPERTIES OF POMFRETS AND HILSA - VENKATARAMAN,, R; KANDORAN, M K; RAJE, C R (Fishery Technology, 2025)
Fresh silver pomfret, black pomfret and hilsa were canned atabsolutely fresh and iced conditions and the qualities of the finalproducts were studied comparatively in relation to th~ initial qualityof the raw materials. Under identical conditions a maximum quantityof cook-drip and nitrogen contents were found to be lost in blackpomfret and minimum in hiJsa. Silver pomfret and black pomfreticed for 3 days gave fairly good products on canning while hilsa cameout only as a satisfactory product on canning after the same icestorage period of the raw material.